High-performance bismuth layered structure piezoelectric ceramic and preparation method thereof
By geometric design and structural optimization of bismuth layered piezoelectric ceramics, the problem of insufficient piezoelectric performance in high temperature environments is solved, and the high Curie temperature and high d33 value are achieved, which significantly improves the piezoelectric performance of the ceramics.
Patent Information
- Application Number
- CN202510061540.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high-temperature piezoelectric ceramic materials cannot take into account both high Curie temperature and high d33 values, resulting in insufficient piezoelectric performance in high-temperature environments.
By geometrically designing the bismuth layered piezoelectric ceramic, the positive transverse piezoelectric constant d31 is used to enhance the longitudinal piezoelectric constant d33, adopt a spherical shell structure and apply longitudinal stress, causing the ceramic sheet to produce a large lateral deformation, thereby improving its effective d33 value.
The effective d33 value of bismuth layered piezoelectric ceramics has been significantly improved, so that they have higher piezoelectric properties in high temperature environments and can meet more stringent application needs.
Smart Images

Figure CN119874364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of piezoelectric ceramic materials, and in particular to a high-performance bismuth layered structure piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics can realize the mutual conversion between mechanical energy and electrical energy, and are an important type of force-electric functional materials. Piezoelectric ceramics are currently widely used in various industrial production and social life, such as ultrasonic transducers, medical imaging, pressure sensing devices, piezoelectric energy harvesting devices, etc. With the rapid development of modern science and technology, piezoelectric ceramic materials are required to serve in extreme environments, such as high-temperature pressure sensors used in nuclear reactors, fuel injection piezoelectric valves used in internal combustion engines, etc. Piezoelectric ceramic materials with ultra-high Curie temperatures must be selected to ensure that piezoelectric ceramics can work normally at higher temperatures and avoid failure problems. Therefore, piezoelectric applications in high-temperature fields have put forward higher requirements for piezoelectric ceramic materials, such as high operating temperature, high resistivity, high voltage electrical performance, and high temperature stability.
[0003] Since the Curie temperature T of piezoelectric ceramics C The higher the piezoelectric coefficient d of the material 33 Therefore, although commonly used high-temperature piezoelectric ceramics, such as bismuth layered piezoelectric ceramics or perovskite-like piezoelectric ceramics, have very high Curie temperatures (>700°C), their d 33 It is generally low (5-30 pC / N), which results in limited sensitivity of the prepared sensor. The serious lack of piezoelectric performance has always been one of the important bottlenecks restricting the development of high-temperature piezoelectric ceramics.
[0004] The Curie temperature of calcium bismuth tantalate-based ceramics (CaBi2Ta2O9, CBTO for short) with bismuth layered structure is as high as 940°C, which can meet the application requirements of high-temperature piezoelectric devices. However, the piezoelectric coefficient d 33 It is about 4-5pC / N. Through sodium, bismuth and cerium doping, Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9 ceramics 33 It can reach 12.8pC / N. From the above, it can be seen that although the calcium bismuth tantalate-based ceramics are doped with sodium bismuth cerium elements, 33 There has been some improvement, but it is still difficult to meet the usage needs.
[0005] Therefore, it is urgent to develop a method that can take into account both high Curie temperature and high d 33 Value of piezoelectric ceramics. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance bismuth layered structure piezoelectric ceramic and a preparation method thereof, so as to solve the problem that the above-mentioned piezoelectric ceramic materials cannot have a high Curie temperature T C and high d 33 The present invention can utilize the higher positive transverse piezoelectric constant d by appropriately designing the piezoelectric ceramic geometry. 31 To significantly increase the effective d of piezoelectric ceramics 33 value.
[0007] To achieve the above object, the present invention provides a high-performance bismuth layered piezoelectric ceramic, the bismuth layered piezoelectric ceramic has a 31 and d 33 The same sign, bismuth layered piezoelectric ceramics are in the shape of spherical shells.
[0008] The unique piezoelectric expansion effect (d 31 and d 33 The same sign) adopts a spherical shell structure design, which applies longitudinal stress to make the ceramic sheet produce a large lateral deformation, and uses the lateral d 31 The piezoelectric constant d of the piezoelectric ceramic is realized by a positive value. 33 enhancement effect.
[0009] The geometrical design of the ceramic sheet of the present invention is not only applicable to 31 and d 33 The same bismuth layered piezoelectric ceramics, this design scheme is also helpful to improve the effective d of other structures, such as perovskite piezoelectric ceramics 33 value, but due to the d 33 and d 31 The positive and negative signs are opposite, and the improvement is relatively low. 33 and d 31 Perovskite piezoelectric ceramics with opposite signs, d 31 and d 33 Bismuth layered piezoelectric ceramics of the same type have better d 33 Value enhancement effect.
[0010] Unlike perovskite piezoelectric ceramics, piezoelectric ceramics with numerous bismuth layer structures have d 31 and d 33 The geometric structure designed by the present invention can make the spherical shell of the piezoelectric ceramic produce a large strain in the lateral direction when the spherical shell is subjected to longitudinal stress. The lateral strain is restrained by the fixing ring, so that a larger longitudinal polarization difference is produced. Therefore, its effective d 33 The value is equivalent to the original ceramic d 33 Several to dozens of times d 31 The superposition of these greatly enhances the piezoelectric properties of the ceramic itself.
[0011] After theoretical derivation, under completely rigid conditions and with bound transverse strain, the transverse stress σ1 and the longitudinal stress σ3 have the following relationship:
[0012]
[0013] Where r is the arc length of the section of the ceramic spherical shell through the center point, and ρ is the curvature of the spherical shell and is greater than 0.
[0014] At this time, the effective 33 Equal to the transverse piezoelectric constant d 31 and the longitudinal piezoelectric constant d 33 The superposition of:
[0015] efficient
[0016] Formula (2) shows that the smaller the curvature, the more effective d 33 However, considering the tightness of the assembly between the piezoelectric ceramic and the lateral fixing device (i.e., the fixing ring), the curvature is set to 1 to 100 mm. -1 This formula shows that the effective d 33 The value can be greatly improved by using a spherical shell structure. 31 and d 33 The sign is opposite, but due to d 31 Effective for 33 The contribution of d is much greater than 33 , so the effective 33 The absolute value of is still increased, but compared with the bismuth layered piezoelectric ceramics, its effective d 33 The increase should be relatively low.
[0017] Preferably, the bismuth layered piezoelectric ceramic has a curvature of 5 to 10 μm. -1 , spherical shell shape with a shell radius of 7 to 20 mm and a thickness of 0.4 to 1 mm.
[0018] Preferably, at room temperature, the effective d 33 The value is above 100pC / N.
[0019] The second aspect of the present invention provides a method for preparing a high-performance bismuth layered structure piezoelectric ceramic, comprising the following steps:
[0020] (1) using bismuth layered piezoelectric ceramic raw materials to prepare pre-sintered powder by a solid phase method;
[0021] (2) The pre-calcined powder is subjected to secondary ball milling, granulation and tableting, and binder removal and sintering in sequence to obtain a ceramic sheet;
[0022] (3) machining the ceramic sheet until a spherical shell-shaped ceramic sheet is formed;
[0023] (4) The spherical shell-shaped ceramic sheet is polarized to obtain a bismuth layered structure piezoelectric ceramic.
[0024] Preferably, the preparation method further comprises assembling the bismuth layered piezoelectric ceramic into a strain device, the strain device comprises a fixing ring and a force-bearing bottom plate, and the spherical shell-shaped bismuth layered piezoelectric ceramic is placed in the fixing ring.
[0025] Preferably, the inner diameter of the fixing ring matches the outer diameter of the spherical shell-shaped bismuth layered structure piezoelectric ceramic, the outer diameter of the fixing ring is 1 to 10 mm larger than its inner diameter, the thickness of the fixing ring is 0.4 to 5 mm, the outer diameter of the force-bearing base plate is the same as the outer diameter of the fixing ring, and the thickness of the base plate is 1 to 3 mm.
[0026] Preferably, after placing the spherical shell-shaped bismuth layered structure piezoelectric ceramic in the fixing ring, an adhesive is added into the fixing ring to bond the spherical shell-shaped bismuth layered structure piezoelectric ceramic to the fixing ring and the force-bearing bottom plate.
[0027] Preferably, a high performance Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 The preparation method of Bi2Ta2O9 piezoelectric ceramics comprises the following steps:
[0028] (1) Preparation of ceramic powder by solid phase method
[0029] The raw materials were respectively prepared according to the above general formula Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9 is weighed and mixed, placed in a polyurethane ball mill (powder: zirconium ball = 1:2-3), and milled in a planetary ball mill for 10-24 hours (rotation speed is 180-350r / min) with anhydrous ethanol as the dispersion medium (powder: anhydrous ethanol = 1:2-3). The mixed slurry is poured out and dried to obtain a dry powder. The dry powder is put into a crucible and pre-sintered at 800-950°C in a box furnace for 3-6 hours to obtain Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9 (CNBCBTO) pre-calcined powder;
[0030] (2) Secondary ball milling
[0031] The pre-calcined powder obtained in step (1) is placed in a polyurethane ball mill, and a dispersion medium is added again, and then placed in a planetary ball mill for secondary ball milling for 10 to 24 hours at a rotation speed of 180 to 350 r / min, and then the slurry is poured out and dried to obtain a dry ceramic powder;
[0032] (3) Granulation and tableting
[0033] The ceramic powder dried in step (2) is fully mixed with 5-10 wt% polyvinyl alcohol binder and then granulated to form evenly distributed particles, which are then pressed into prefabricated ceramic discs with a diameter of 8-20 mm and a thickness of 0.8-5 mm under a uniaxial pressure of 10-25 MPa;
[0034] (4) Debinding sintering
[0035] Debinding the prefabricated ceramic disc in step (3) at a temperature of 400-6000° C., and then sintering at a temperature of 1100-1300° C. for 4-6 hours to form a sintered ceramic disc;
[0036] (5) Spherical shell processing
[0037] The sintered ceramic disc is polished by mechanical processing to prepare a curvature of 5 to 10 m. -1 , the spherical shell has a radius of 7 to 20 mm and a thickness of 0.4 to 1 mm, and is then silver polarized for later use;
[0038] (6) Polarized by silver
[0039] The ceramic disc processed into a spherical shell in step (5) is brushed with a silver paste with a concentration of 5 to 15 wt%, and then sintered at a temperature of 650 to 750° C. for 15 minutes to prepare a sample, and polarized in an oil bath between room temperature and 200° C. to prepare a piezoelectric ceramic. The polarization voltage is gradually increased from a low voltage to a predetermined voltage, the polarization field strength is 7 to 10 kV / mm, and the holding time is 15 to 30 minutes.
[0040] (7) Assembly
[0041] The polarized spherical shell piezoelectric ceramic is placed in the inner diameter of the fixing ring, and the spherical shell piezoelectric ceramic is bonded to the fixing ring and the stress-bearing bottom plate using epoxy resin and fixing agent to complete the assembly.
[0042] Therefore, the present invention adopts the above-mentioned high-performance bismuth layered structure piezoelectric ceramic and its preparation method, which has the following beneficial effects:
[0043] (1) The bismuth layered piezoelectric ceramics of the present invention have a 31 and d 33 The same sign characteristics, after geometric structure design, can be used to apply longitudinal force to make the positive transverse piezoelectric constant d 31To enhance the longitudinal piezoelectric constant d of the ceramic 33 . Specifically, ordinary CNBCBTO (Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9) Bismuth layered piezoelectric ceramics 33 9.4pC / N. After adopting the geometric design of the present invention, the d of CNBCBTO ceramics can be 33 The value is increased to 140pC / N, and the effective 33 The value has been significantly improved.
[0044] (2) The geometric structure design of the present invention only utilizes the d 31 and d 33 The same sign characteristics do not change the inherent properties of the piezoelectric ceramic material, so that the piezoelectric ceramic material can still maintain the ultra-high Curie temperature T C In the case of 33 The piezoelectric ceramic material prepared by the present invention has both high Curie temperature and high d 33 value, while meeting the ability to be used at high temperatures.
[0045] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the X-ray diffraction pattern of CNBCBTO ceramic material;
[0047] Figure 2 This is a scanning electron microscope photo of CNBCBTO ceramic material;
[0048] Figure 3 This is the high temperature dielectric curve of CNBCBTO ceramic material;
[0049] Figure 4 It is the stress current test and electric field displacement test of CNBCBTO ceramic material; Figure A is the stress current test principle diagram; Figure B is the input stress curve and output current curve; Figure C is the relationship between current and stress; Figure D is the electric field displacement test principle diagram; Figure E is the input voltage curve and output displacement curve; Figure F is the relationship between displacement and voltage;
[0050] Figure 5 The geometric structure design diagram of CNBCBTO ceramics; Figure A is a cross-sectional left view of the design structure; Figure B is a top view of the design structure;
[0051] Figure 6 is the piezoelectric constant d of CNBCBTO ceramic material before and after design33 ; Among them, 1# is ordinary CNBCBTO ceramic without restraint; 2# is CNBCBTO ceramic after structural design;
[0052] Figure 7 This is the appearance of CNBCBTO ceramic after machining;
[0053] Figure 8 This is the appearance diagram of the strain device. DETAILED DESCRIPTION
[0054] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0055] Example 1
[0056] This embodiment provides a method for preparing a common piezoelectric ceramic. Specifically, the general formula of the common piezoelectric ceramic is Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9 (abbreviated as CNBCBTO), the preparation method of the CNBCBTO ceramic comprises the following steps:
[0057] (1) Preparation of CNBCBTO ceramic powder by solid phase method
[0058] The raw materials were weighed and mixed according to the general formula, and then placed in a polyurethane ball mill (powder: zirconium ball = 1:2), and anhydrous ethanol as a dispersion medium was added (powder: anhydrous ethanol = 1:3), and then placed in a planetary ball mill for 24 hours until the mixture was uniformly mixed, with a rotation speed of 300 r / min, the uniformly mixed slurry was poured out and dried to obtain a dry powder, the dry powder was placed in a crucible, and the temperature was raised to 900°C in a box furnace for pre-calcination for 5 hours to obtain a pre-calcined powder;
[0059] (2) Secondary ball milling
[0060] The calcined powder prepared in step (1) is placed in a polyurethane ball mill (powder: zirconium ball = 1:2), and anhydrous ethanol as a dispersion medium is added again (powder: anhydrous ethanol = 1:3), and then placed in a planetary ball mill for secondary ball milling for 20 hours at a speed of 200 r / min, and then the slurry is poured out and dried to obtain a dry ceramic powder;
[0061] (3) Granulation and tableting
[0062] The ceramic powder dried in step (2) is fully mixed with 8 wt % polyvinyl alcohol binder and then granulated to form evenly distributed particles, which are then pressed into prefabricated ceramic discs with a diameter of 10 mm and a thickness of 3.0 mm under a uniaxial pressure of 20 MPa;
[0063] (4) Debinding sintering
[0064] Debinding the prefabricated ceramic disc in step (3) at a temperature of 500° C., and then sintering at a temperature of 1200° C. for 5 hours to form a sintered ceramic disc;
[0065] (5) Polarized by silver
[0066] The sintered ceramic disc in step (4) was brushed with silver paste with a concentration of 10wt%, and then sintered at a temperature of 700°C for 12 minutes to prepare a sample, and polarized in an oil bath at 100°C to prepare a piezoelectric ceramic. During the polarization process, the polarization electric field gradually increased from a low electric field to a predetermined polarization electric field of 8kV / mm, and the holding time was 20 minutes.
[0067] Example 2
[0068] This embodiment provides a method for preparing a high-performance bismuth layered piezoelectric ceramic. Specifically, the general formula of the bismuth layered piezoelectric ceramic is Ca 0.6 (Na 0.5 Bi 0.3 Ce 0.2 ) 0.4 Bi2Ta2O9 (abbreviated as CNBCBTO), the preparation method of the CNBCBTO ceramic comprises the following steps:
[0069] (1) Preparation of Lithium Cerium LaTiO3 Ceramic Powder by Solid Phase Method
[0070] The raw materials were weighed and mixed according to the above general formula, placed in a polyurethane ball mill (powder: zirconium ball = 1:2), with anhydrous ethanol as the dispersion medium (powder: anhydrous ethanol = 1:3), and then placed in a planetary ball mill for 24 hours (rotation speed of 300r / min), the mixed slurry was poured out and dried to obtain dry powder, the dry powder was put into a crucible, and the temperature was raised to 900°C in a box furnace for pre-calcination for 3 to 6 hours to obtain CNBCBTO pre-calcined powder;
[0071] (2) Secondary ball milling
[0072] The calcined powder obtained in step (1) is placed in a polyurethane ball mill (powder: zirconium ball = 1:2), and anhydrous ethanol as a dispersion medium is added again (powder: anhydrous ethanol = 1:3), and then placed in a planetary ball mill for secondary ball milling for 20 hours at a speed of 200 r / min, and then the slurry is poured out and dried to obtain a dry ceramic powder;
[0073] (3) Granulation and tableting
[0074] The ceramic powder dried in step (2) is fully mixed with 8 wt % polyvinyl alcohol binder and then granulated to form evenly distributed particles, which are then pressed into prefabricated ceramic discs with a diameter of 10 mm and a thickness of 3.0 mm under a uniaxial pressure of 20 MPa;
[0075] (4) Debinding sintering
[0076] Debinding the ceramic disc prefabricated in step (3) at a temperature of 500° C., and then sintering at a temperature of 1200° C. for 5 hours to form a sintered ceramic disc;
[0077] (5) Spherical shell processing
[0078] The sintered ceramic disc was polished by mechanical processing to produce a curvature of 8m. -1 , the spherical shell has a radius of 11 mm and a thickness of 0.6 mm, and is then silver polarized for later use;
[0079] (6) Polarized by silver
[0080] The ceramic disc processed into a spherical shell in step (5) was brushed with a silver paste with a concentration of 10 wt %, and then sintered at a temperature of 700° C. for 15 minutes to prepare a sample. The sample was polarized in an oil bath at 100° C. to prepare a piezoelectric ceramic. The appearance of the piezoelectric ceramic was shown in FIG. Figure 7 The polarization voltage is gradually increased from low to the predetermined polarization field strength of 8 kV / mm, and the holding time is 20 minutes.
[0081] (7) Assembly
[0082] The specific process is as follows: Use a transverse strain fixing ring, which is a metal high-hardness ring material. Its inner diameter is basically the same as the diameter of the spherical shell piezoelectric ceramic. The outer diameter of the fixing ring is 8mm larger than the inner diameter and the thickness is 3mm. The force-bearing bottom plate is a metal conductive plate with the same diameter as the outer diameter of the transverse strain fixing ring and a thickness of 3mm to withstand the downward pressure of the spherical shell piezoelectric ceramic. Put the polarized spherical shell piezoelectric ceramic into the inner diameter of the fixing ring, and use epoxy resin and fixing agent to bond the spherical shell piezoelectric ceramic to the fixing ring and the bottom plate to complete the assembly. See the appearance of the strain device. Figure 8 .
[0083] Example 3
[0084] The materials prepared in Example 1 and Example 2 were subjected to structural characterization and performance testing.
[0085] The test process is as follows: After standing for 24 hours in an environment with a room temperature of 25°C and a humidity of 45-65% RH, the structural characteristics and piezoelectric characteristics (d33 and d 31 It should be noted that the above test methods are commonly used in the art and will not be described in detail here.
[0086] (1) The phase structure of the high-performance CNBCBTO ceramics prepared in Example 2 was analyzed by X-ray diffractometer (XRD, X'Pert Pro MPD, BVPANalytical). Figure 1 The results show that CNBCBTO ceramics are a single bismuth layered structure, which corresponds well to the theoretical peak of the orthorhombic A21am phase, and there is no second phase.
[0087] (2) The surface morphology of the CNBCBTO ceramics prepared in Example 2 was observed using a scanning electron microscope (SEM, Apreo S, Thermo Scientific). Figure 2 The results show that the CNBCBTO ceramic material shows densely packed grains, the grain size is relatively uniform, and the grains are closely arranged and dense.
[0088] (3) The high temperature dielectric temperature curve and dielectric loss of CNBCBTO ceramic material were tested using an ultra-high temperature dielectric impedance thermometer (DMS-1650, Partulab). Figure 3 The results show that: with the increase of the measurement temperature, CNBCBTO ceramics gradually transform from ferroelectric phase to paraelectric phase, the Curie temperature of phase transition is about 906℃, and the dielectric loss of CNBCBTO ceramics gradually increases with the increase of temperature.
[0089] (4) The forward and reverse piezoelectric constants d of CNBCBTO ceramic materials at room temperature were tested using pressure current test and electric field displacement test methods. 31 and d 33 , see Figure 4 The results show that: the d 31 and d 33 The current signals are completely in phase, indicating that in CNBCBTO ceramic materials, d 31 and d 33 This is the same as the d in conventional perovskite piezoelectric ceramics. 31 and d 33 The characteristics of opposite signs are completely different; the displacement signal also shows that d 31 and d 33 The same sign characteristics confirm that its positive and negative piezoelectric coefficients have the same characteristics. After calculation, the d 31 and d 33 They are 5.4pC / N and 12.8pC / N respectively.
[0090] (5) Figure 5 The geometric structure design used in this experiment is shown in Figure 1. A and B are the longitudinal section and top view, respectively. 33 The room temperature piezoelectric properties of CNBCBTO ceramics were tested by a piezoelectric tester (ZJ-3A). Figure 6 The conventional CNBCBTO ceramic prepared in Example 1 is marked as 1#, and the fixed transverse strain ceramic with geometric structure design in Example 2 is marked as 2#. The results show that the piezoelectric constant d of the CNBCBTO ceramic sample 1# is 33 The piezoelectric constant d of the 2# ceramic sample is 9.4pC / N. 33 It is 140pC / N. This shows that after adopting the geometric structure design of the present invention, the piezoelectric performance of CNBCBTO ceramics is improved. 33 Can be upgraded to the original d 33 Nearly 14 times.
[0091] Therefore, the design method of the present invention greatly enhances the piezoelectric properties of the bismuth layered structure ceramic itself, and is expected to be applied to various piezoelectric devices. In addition, the structural design can also be used for perovskite piezoelectric ceramics, although its d 31 and d 33 The sign is opposite, but when the transverse strain is fixed, the transverse stress of the spherical shell structure is much greater than the normal longitudinal stress, so d 31 The contribution can reach several to dozens of times, resulting in the ceramic showing an ultra-high negative effective d 33 , but its 33 The absolute value of the increase should be lower than that of the bismuth layered perovskite structure.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A high-performance bismuth layered piezoelectric ceramic, characterized in that: Bismuth layered piezoelectric ceramics 31 and d 33 The same sign, bismuth layered piezoelectric ceramics are in the shape of spherical shells.
2. The high-performance bismuth layered piezoelectric ceramic according to claim 1, characterized in that: Bismuth layered piezoelectric ceramics have a curvature of 5 to 10 μm -1 , spherical shell shape with a shell radius of 7 to 20 mm and a thickness of 0.4 to 1 mm.
3. The high-performance bismuth layered piezoelectric ceramic according to claim 1, characterized in that: At room temperature, the effective d 33 The value is above 100pC / N.
4. A method for preparing a high-performance bismuth layered piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) using bismuth layered piezoelectric ceramic raw materials to prepare pre-sintered powder by a solid phase method; (2) The pre-calcined powder is subjected to secondary ball milling, granulation and tableting, and debinding and sintering in sequence to obtain a ceramic sheet; (3) machining the ceramic sheet until a spherical shell-shaped ceramic sheet is formed; (4) The spherical shell-shaped ceramic sheet is polarized to obtain a bismuth layered structure piezoelectric ceramic.
5. The method for preparing a high-performance bismuth layered structure piezoelectric ceramic according to claim 4, characterized in that: The preparation method also includes assembling the bismuth layered structure piezoelectric ceramic into a strain device, the strain device includes a fixed ring and a force-bearing bottom plate, and the spherical shell-shaped bismuth layered structure piezoelectric ceramic is placed in the fixed ring.
6. The method for preparing a high-performance bismuth layered structure piezoelectric ceramic according to claim 5, characterized in that: The inner diameter of the fixed ring matches the outer diameter of the spherical shell-shaped bismuth layered structure piezoelectric ceramic. The outer diameter of the fixed ring is 1 to 10 mm larger than its inner diameter. The thickness of the fixed ring is 0.4 to 5 mm. The outer diameter of the force-bearing base plate is the same as that of the fixed ring. The thickness of the force-bearing base plate is 1 to 3 mm.
7. The method for preparing a high-performance bismuth layered piezoelectric ceramic according to claim 6, characterized in that: After placing the spherical shell-shaped bismuth layered structure piezoelectric ceramic in the fixing ring, an adhesive is added into the fixing ring to bond the spherical shell-shaped bismuth layered structure piezoelectric ceramic to the fixing ring and the stress-bearing bottom plate.